An audit around preferred place of death: one UK hospice experience. Issue 2 (1st September 2011) - Walker, Susan; Read, Susan; Priest, Helena
Abstract : Introduction: According to the End of Life Care Strategy, good end of life care includes choosing a place of care for one's death. It is easy to assume that all hospice patients discuss their wishes and that plans for death are recorded. The audit data in this paper, however, suggests that such planning is not universal and asks questions about why this might be so. Aims: To present an audit of 150 hospice case notes to show the documentation of patients' preferred place of death over a 2 year period. Methods: As phase one of a PhD research study, case notes of deceased patients were accessed from January 2008 (n=50); January 2009 (n=50) and January 2010 (n=50) during September – November 2010. Data collected included actual place of death, whether preferred place of death was documented, whether preferences were achieved, whether patients had conversations about end of life care options; whether wishes were reviewed and which professionals recorded information. The 2 year time frame represented a range of experiences within the hospice context. Descriptive statistics were used for analysis. Results: Results illustrated that place of death was varied; that preferred place of death was recorded in only 18.7% of cases and of this very small number whose wishes were documented, the majority (89.3%) died in their chosen location. Only 10.6% of the sample recorded conversations about preferences, and reviews were infrequent (21%) with few changes of preference. Conclusions: This research demonstrates that identification, documentation and review of preferred place of death was achieved for only a small percentage of patients of this hospice during 2008–2010. This prompts further research questions around why this is so.